(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
In this article - irrigated serozemno-meadow, the soil water-physical and agro-chemicals agromeliorativ family properties and status information obtained based on the condition of soil on the basis of a detailed study of the territory agromeliorativ maintaining, monitoring, improvement directed them to research-based recommendations should be used in the practice and development of on activities and recommendations are given